Pendampingan Proses Pembuatan Soal Berbasis Computational Thinking kepada Guru pada Guru-Guru Tingkat SD dan SMP Kecamatan Sakra, Kabupaten Lombok Timur - Ni Ketut Sriwinarti; Apriani Apriani; Diah Supatmawati; Kartarina Kartarina; Ismarmiaty Ismarmiaty (LPPM Universitas Bumigora, 2022)
Thinking about computing or Computational Thinking (CT) is one of the problem solving techniques that is very important today to prepare the next generation to be competitive in this digital economy era. This skill teaches students how to think the way scientists think, to solve real-world problems. In training or familiarizing children with CT, this can be done by including or adding CT to the learning strategy. The intended strategy can be related to the packaging of the material, the learning media used, or an interesting learning model that can familiarize children with CT. The learning media used are expected to help children understand the subject matter. For early childhood, learning media has a vital role in learning. This is because at that age children are still at the stage of learning while playing. On August 6, 2019, Bumigora University signed a charter of cooperation with the coordination of the national committee (National Board Organization (NBO) bebras Indonesia), where for the next 5 (five) years Bumigora University will become a partner in realizing PANDAI students . PANDAI, is the name chosen as the movement to socialize CT, which stands for Pengjar Digital Era Indonesia. The PANDAI Movement training in collaboration with Bumigora University is also the first teacher training to be held in the entire West Nusa Tenggara region, involving approximately 400 elementary and junior high school teachers. Service activities related to Computational Thinking have been carried out. The results of the implementation have been evaluated with the results that most of the teacher participants agreed to apply the results of the training related to Computational Thinking to students and also most of the participants agreed to join the follow-up programs from Bebras. The implementation stage for students is still unable to carry out the service team due to the current pandemic situation, but with the continuation of the activities carried out by the UBG bureau with NBO Bebras. It is hoped that this activity can run continuously and be supported positively by the parties involved.